Effectiveness and Safety of an Intravenous Immune Globulin (IVIG) Preparation in Post-exposure Prophylaxis (PEP) Against Measles in Infants - Kohlmaier, Benno; Holzmann, Heidemarie; Stiasny, Karin; Leitner, Manuel; Zurl, Christoph; Strenger, Volker; Kundi, Michael; Zenz, Werner (Frontiers in Pediatrics, 2021)
Background: Administration of measles virus (MV)-specific IgG as post-exposure prophylaxis (PEP) is known to effectively prevent measles. Since the introduction of active immunisation against measles, the levels of MV-specific IgG antibodies in the population have dropped. Therefore, the concentration of MV-specific antibodies in immunoglobulin products derived from human plasma donors has declined as the proportion of vaccinated donors has increased. Literature on the effectiveness of PEP with current available immunoglobulins is limited. Here we examine the effectiveness of 400mg/kg intravenous immunoglobulin (IVIG) (IgVena®, Kendrion) as PEP in infants during a measles outbreak in Austria, 2019. Methods: After exposure to a highly contagious measles patient, identified infants were evaluated for eligibility for IVIG PEP. Infants were tested for measles maternal antibodies, if the result was expected to be available within 72 hours after exposure. IVIG was administered to eligible infants with negative maternal IgG antibody levels (n=11), infants with protective levels but result beyond 72 hours (n=2) and infants not tested for maternal IgG antibodies (n=52). Telephone enquiries were made asking for measles infection. Effectiveness was calculated using exact logistic regression. Samples of 4 out of 7 used IVIG batches were tested for MV-neutralizing antibody capacity. Results: In 63 (96.9%) of 65 infants PEP with IVIG was administered. The parents of two infants declined IVIG PEP. None of the infants with IVIG PEP got measles or symptoms suggestive for measles, but both infants who did not receive PEP were infected. Effectiveness of IVIG PEP was calculated to be 99.3% (CI 95%: 88.7-100%). No serious adverse event of IVIG treatment was observed. The investigation on MV-neutralizing antibody capacity showed a geometric mean titre ranging from 10.0 to 12.7 IU/ml, resulting in a 1.57 to 2.26-fold higher concentration than postulated as minimum level for immunity. Conclusions: Our findings suggest that the used IVIG preparation provided an at least non-inferior protection rate compared to IVIG preparations derived from donors before the global introduction of standard active immunisation against measles.